Development of LKPD assisted by phet simulation on material form of energy and their changes to improve creative thinking ability of students at SMP Negeri 2 Sunggal - Febrina Br Ginting; Hudson Sidabutar (Educenter : Jurnal Ilmiah Pendidikan, 2022)
Student Worksheet (LKPD) is one way to support and activate learning activities so that students and teachers can interact more effectively, which can improve learning activities and student achievement. Because PhET media encourages creativity, it can help students' creative thinking skills. 4D technique, PhET Simulation helps the development of LKPD. In this study, data collection used observational methods, questionnaires, tests, and documentation methods. In this study, descriptive analysis and N-gain test were used for data analysis. Two material experts, learning experts, design experts, seventh grade science teachers, and 32 seventh grade students of SMP N 2 Sunggal became the sample. Based on the approval of LKPD, learning experts, and learning materials experts and design experts, class VII science teachers and 32 students of class VII SMP N 2 Sunggu. Based on expert validation, learning experts and LKPD material design experts, the participant's response was very good and the LKPD materials assisted by PhET Simulation could improve students' creative thinking skills, which can be seen from the N-gain calculation, which is 0.71 high categories.